(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Gastrointestinal Stromal tumors (GIST) are uncommon primary mesenchymal tumors arising from the gastrointestinal tract. The duodenum location is unusual. The authors present a case of duodenal GIST, mimicking a pancreatic tumor. Preoperatively computed tomography (CT) revealed a hypervascular mass of 10 cm in diameter, in the pancreatic head. Endoscopic examination showed erosion in duodenal mucosal with local bleeding. The patient underwent sucessfully pylorus-preserving pancreaticoduodenectomy.